2005
DOI: 10.1002/gps.1284
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment in dementia

Abstract: This data underlines the degree of unmet need in the community dwelling elderly with dementia and the importance of developing a spectrum of services on the basis of the actual needs identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 32 publications
7
83
0
Order By: Relevance
“…Previous analyses of our data showed that community-dwelling PWD had on average about nine unmet needs that should be addressed, and there were no significant differences in the number of unmet needs between patients who lived alone and those who did not [26]. Other studies demonstrated that PWD who lived alone had even more unmet needs than those living together with another person [4,8]. PWD who live alone, particularly if they have no informal caregiver, may require special support in order to gain access to the treatment and care services that address their individual needs comprehensively.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Previous analyses of our data showed that community-dwelling PWD had on average about nine unmet needs that should be addressed, and there were no significant differences in the number of unmet needs between patients who lived alone and those who did not [26]. Other studies demonstrated that PWD who lived alone had even more unmet needs than those living together with another person [4,8]. PWD who live alone, particularly if they have no informal caregiver, may require special support in order to gain access to the treatment and care services that address their individual needs comprehensively.…”
Section: Discussionmentioning
confidence: 43%
“…In addition, they have more unmet needs, less access to health care, higher risks of problems with medication, untreated medical conditions, falls and injuries, earlier nursing home transition, and inadequate self-care such as malnutrition, poor hygiene, or inadequate clothing or housing. These risks increase with the progression of the disease [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The three terms are similar in meaning and may arise due to the unmet needs associated with the communication challenges of the PWD. [1,17,24] Caregivers often enter the role of caring for PWD without fully understanding the consequences of ineffective communication which are linked to problem behaviours. Goldberg [25] pointed out that problem behaviours exist among PWD who live in the community as well as among those who live in institutions.…”
Section: Problem Behaviours and Communicationmentioning
confidence: 99%
“…Social activities during midlife are also related to a reduced dementia risk (Carlson et al , 2008 ). Community-dwelling older people with dementia report that their needs for social interaction and participation in activities are largely unmet (Meaney et al , 2005 ). Those with higher age, lower mini mental state examination (MMSE) scores, and living alone have greater levels of unmet needs (Meaney et al , 2005 ).…”
Section: Lonelinessmentioning
confidence: 99%
“…Community-dwelling older people with dementia report that their needs for social interaction and participation in activities are largely unmet (Meaney et al , 2005 ). Those with higher age, lower mini mental state examination (MMSE) scores, and living alone have greater levels of unmet needs (Meaney et al , 2005 ). These aspects result unfortunately in a higher risk of moving into a nursing home which is an even more impoverished environment, which will be addressed in the next section.…”
Section: Lonelinessmentioning
confidence: 99%